2021
DOI: 10.35741/issn.0258-2724.56.6.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Social Stigma on Tuberculosis Care: Case Studies in Maha Sarakham Province, Thailand

Abstract: Tuberculosis (TB) is a public health issue that relies on the participation of health networks and the care of tuberculosis patients systematically and effectively. This study aimed to investigate the effects of social stigma on continuous tuberculosis patient care. This qualitative research study employed a case study approach to investigate the effects of social stigma on the continuous tuberculosis patient care in Maha Sarakham Province, Thailand. The current study also explored tuberculosis patients’ healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…There are two types of rituals in Thai society, the common rituals where similar patterns are being implemented throughout the country, and local rituals with specific actions unique to a specific area. However, the elements of both types of rituals are the same, based on the beliefs, which are the foundation of the actions, the master of the rituals, steps, and participants (Thammawatra, 1987).…”
Section: Boon Duan Si Melody (Phawet Procession)mentioning
confidence: 99%
See 1 more Smart Citation
“…There are two types of rituals in Thai society, the common rituals where similar patterns are being implemented throughout the country, and local rituals with specific actions unique to a specific area. However, the elements of both types of rituals are the same, based on the beliefs, which are the foundation of the actions, the master of the rituals, steps, and participants (Thammawatra, 1987).…”
Section: Boon Duan Si Melody (Phawet Procession)mentioning
confidence: 99%
“…There are two types of rituals in Thai society, including common rituals, which have similar patterns and actions throughout the whole country, and local rituals, which are unique to each locality. However, the elements of both types of rituals remain the same, which consist of the belief, which is the base of the action, the master of the rituals, the methods of carrying out the rituals, and the participants (Thammawatra, 1987). Khunpakdee (1987) studied the beliefs of Thai people in the past and concluded that beliefs refer to the status that the individuals place their confidence in, agree with, and prepare to follow and pass on to others to instill the confidence in others to agree and follow without consideration of whether they can be logically proven or not.…”
Section: Introductionmentioning
confidence: 99%